Idea elektronicznych atlasów organizacji - Stępniak, Cezary (The Idea of the Electronic Atlas of Organizations, 2007)
The paper shows the concept of the Electronic Atlas of Organizations. The basic aim of the idea is to use proposed atlases for functional, informational and technical development of modern information systems. The concept is based on using cartographic tools in Business Information System. The consideration begins with information functions of information system. The elements of mentioned six functions are presented. The presentation focuses on showing potential added possibilities reached by using cartographic tools. Theoretically application of mentioned tools can develop each of analyzed functions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 254-265